A Band from the "Blue" - Padmanabha Vijayan (Archive of Urological Research - Peertechz Publications, 2023)
Several lesions of the bladder are incidental findings and a few of them are seen against a background of bladder outlet obstruction. Tuberculosis of the bladder is associated with characteristic lesions and changes. Presented here is a never-seen-before bladder lesion in a patient presenting with symptoms of Bladder Outlet Obstruction due to an enlarged tuberculous prostate, and no evidence of tuberculous cystitis.